Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment. (June 2023) - Lee, Jooyeon; Baek, Hyosin; Jang, Jimin; Park, Jaehyun; Cha, Sang-Ryul; Hong, Seok-Ho; Kim, Jieun; Lee, Jong-Hee; Hong, In-Sun; Wang, Seung-Jun; Lee, Ji Young; Song, Myung Ha; et al.
Abstract: Alveolar epithelial cells (AECs) are vulnerable to injury, which can result in epithelial hyperplasia, apoptosis, and chronic inflammation. In this study, we developed human induced pluripotent stem cell (hiPS) cell-derived AECs (iAECs) and the iAECs based organoids (AOs) for testing AEC toxicity after chemical exposure. HiPS cells were cultured for 14 days with differentiation medium corresponding to each step, and the iAECs-based AOs were maintained for another 14 days. SFTPC and AQP5 were expressed in the AOs, and mRNA levels of SOX9, NKX2.1, GATA6, HOPX, and ID2 were increased. The AOs were exposed for 24 h to nine chemical substances, and IC50 values of the nine chemicals were determined using MTT assay. When the correlations between iAECs 2D culture and AOs 3D culture were calculated using Pearson's correlation coefficient r value, the nine chemicals that caused a significant decrease of cell viability in 3D culture were found to be highly correlated in 2D culture. The cytotoxicity and nitric oxide release in AO cultured with macrophages were then investigated. When AOs with macrophages were exposed to sodium chromate for 24 h, the IC50 value and nitric oxide production were higher than when the AOs were exposed alone. Taken together, the AO-based 3D culture system provides a useful platform for understanding biological characteristics of AECs and modeling chemical exposures. Graphical abstract: Unlabelled Image Highlights: hiPS cells-derived AOs are highly correlated with hiPS cells-derived with AECs. Chemical exposed to AOs cultured with hM-like cells susceptible to NO production. AOs-based system is useful for understanding biological characteristics of alveolar epithelial cells.